Secondary school prefects’ democratic competences in Akure City, Nigeria (2023)
This research work was carried out to unravel democratic cultural competence of senior secondary school students- prefects in Akure City, Ondo State, Nigeria. Three hundred and ninety (390) senior secondary school prefects from twenty-eight (28) secondary schools participated in this study and the data collected were analysed using simple tables, frequency count, graphs, percentages and mean deviation. According to the study findings, it was found that the school prefects possessed high level of democratic knowledge, values, attitude arid the school prefects' interest in politics was high while their democratic skills was moderate. This is not the focus of this paper. Therefore, this study recommended that secondary schools' administration should be all inclusive in such a way that it will afford students the opportunity of participating in the decision-making process, while teachers should create a friendly and democratic learning environment where the interest of the learners is the centre-piece of the learning activities by emphasizing students-centred methods of teaching.